ANALISIS EKSPOR-IMPOR DAN INDEKS HARGA KONSUMEN PADA PERTUMBUHAN EKONOMI INDONESIA - Darman Darman (Jurnal Manajemen Indonesia, 2016)
This study aims to assess and analyze the Effect of Export, Impor and Consumer Price Index in economic growth in Indonesia from 2000 to 2014. This research uses quantitative descriptive approach with the nature of verification explanatory method. The data used are secondary data in the form of Export, Import, and the Consumer Price Index of Indonesian Economic Growth (GDP) in 2000-2014. The results showed that export push the GDP more effectively: compared to import sector and CPI. Regression analysis showed that the constant value of GDP was 0.526. Also, the Export Coefficients value is 0.015, the Import Coefficients value is -0,026 and CPI is -0.2303. Meaning that 1 percent of the value of exports will increase GDP by 1.5 percent, 1 percent of imports will lower the value of GDP by 2.6 percent and 1 percent of the CPI will lower the value of GDP by 23.03 percent. This means that Exports variable boots GDP more effective from Import sector and the Consumer Price Index. Significance test results showed that the variables of export, import and CPI jointly influence economic growth (GDP) with the alpha (a) of 5% as shown by the F-statistic significant value of 0.74, greater than a=0,05. In other words, the independent variabel (exports, imports and CPI) jointly affect the dependent variable (GDP)